Phytochemical Profiling and Biological Activities of Two Helianthemum Species Growing in Greece - Evgenia Panou; Konstantia Graikou; Nikolaos Tsafantakis; Fanourios-Nikolaos Sakellarakis; Ioanna Chinou (MDPI AG, 2024)
Helianthemum nummularium (HN) and Helianthemum oelanticum subsp. incanum (HO) are plant species, among Cistaceae, that are highly distributed in the Mediterranean region. In the current study, extracts of the aerial parts from both species have been analyzed phytochemically. The non-polar extract analysis resulted in the identification of 15 compounds in each species, mainly terpene and fatty acid derivatives, through GC-MS. The methanolic extract analysis, conducted through UHPLC-MS/MS, led to the identification of 39 metabolites in HN and 29 in HO, respectively, the majority of which were phenolics. Among the identified compounds, several have also been isolated and structurally determined (from HN: rutin, linoleic acid, gallic acid, and isoquercetin, and from HO: quercetin-3-O-(2"-O-galloyl)-galactopyranoside, methyl gallate, catechin-3-O-glucopyranoside, and astragalin, while hyperoside, and cis- and trans-tiliroside have been determined in both species). Furthermore, the methanolic extracts of HN and HO displayed a high total phenolic content (177.2 mg GA/g extract and 150.6 mg GA/g extract, respectively) and considerable free-radical scavenging activity against the DPPH radical (94.6% and 94.0% DPPH inhibition, respectively). Antimicrobial testing showed stronger inhibition of HN against Gram (+) bacterial strains (MIC values 0.07-0.15 mg/mL), while both extracts exhibited low tyrosinase-inhibitory activity. Considering the lack of studies conducted on the chemistry and biological activities of the genus Helianthemum, the chemical characterization of extracts could contribute to new sources of bioactive metabolites to be explored and exploited for further potential applications such as food and/ or the cosmetic industry.